PENGARUH KECERDASAN SPIRITUAL DAN KECERDASAN EMOSIONAL TERHADAP KINERJA AUDITOR YANG DIMODERASI OLEH REMUNERASI PADA KANWIL DJP DAERAH ISTIMEWA YOGYAKARTA - Daning Husadari; Priyastiwi Priyastiwi (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
The purpose of this study was to determine the effect of spiritual intelligence variables, emotional intelligence variables, remuneration variables, remuneration moderating variables on the effect of spiritual intelligence, and emotional intelligence remuneration moderating variables on the performance of tax auditors in the DJP Kanwil Daerah Istimewa Yogyakarta. The method in this research is a quantitative descriptive method. The population of this study were 105 tax auditors in the Kanwil DJP Daerah Istimewa Yogyakarta, The technique of multiplying the sample using the saturated sample method is to make the entire population part of the sample. The data collection method used is using a questionnaire and for data analysis using a structural equation model. The results of the study show that spiritual intelligence, emotional intelligence, remuneration, remuneration moderate the effect of spiritual intelligence, and remuneration moderates the effect of emotional intelligence on the performance of tax auditors. Spiritual intelligence has a positive effect on the performance of the tax auditor. Emotional intelligence has a positive effect on the performance of the tax auditor. Remuneration has a positive effect on the performance of the tax auditor. Remuneration moderates the influence of spiritual intelligence has a positive effect on the performance of the tax auditor. Moderating the remuneration of the influence of emotional intelligence has a positive effect on the performance of the tax auditor.